'Speak at this': an approach to the completion of Speech Acts during interactive Shakespeare performances in schools. Issue 2 (4th May 2018) - Bell, Henry
Abstract : In 2014, in a secondary school in Scarborough, North Yorkshire, a performance of Romeo and Juliet took place in the school hall. An audience of teenagers sat on plastic blue chairs arranged in-the-round. During the 'balcony scene' the performer playing Romeo asked a member of the audience, 'Shall I hear more, or shall I speak at this?' The audience member urged him to 'hear more'. This article interrogates that moment in performance, the process that was required to achieve it and the validity of it as a successfully completed speech act. Speech act theory has been used as a valuable method for Shakespearean textual analysis but this article investigates the merits of its application as a rehearsal technique: What training methods augment the performative nature of audience address? How can current theoretical concerns in audience studies temper the application of speech act theory in this context to provide an open and interactive Shakespeare performance atmosphere for young people? In order to address these questions, the argument will draw upon media and data from a large-scale Practice as Research project produced by the University of Hull and the Stephen Joseph Theatre in Yorkshire in 2014.